ANALYSIS OF REVITALISATION MODEL BEHAVIOUR FOR THERMAL POWER PLANTS IN DIFFERENT GEOGRAPHICAL AREAS - Bricl Martin; Avsec, Jurij (Journal of Energy Technology, 2025)
The implementation of renewable sources for electricity production into the energy portfolio of European countries has been a priority in recent years, especially taking into account the current geo-political changes. Even though coal is the fuel of the past, its use cannot be put aside that easily; firstly, because of the high fluctuation of electricity production from renewable sources, and secondly because of the possible negative economic impact on the economy resulting from a change in electricity prices when exiting coal. Based on the Rankine process, the authors of this paper designed a solar tower installation with a heliostat field, which enables electricity production based on solar irradiation. This combination also foresees an additional installation for flue gas desulphurisation. This combination of three processes is named the ‘revitalisation model’ for thermal power plants (TPPs). Based on the computer model and energy market parameters, the authors tested the ‘revitalisation model’ for pessimistic and optimistic scenarios. In the scope of the paper, the authors analyse the performance of the proposed ‘revitalisation model’ for three different geographical locations – Berlin in Germany, Wuwei in China, and Hyderabad in India. The results of the analysis are described and shown graphically.